Determinants of income inequality and their impact on violent crime in Nigeria - Guza, Garba Mohammed (2020)
The main objective of this thesis is to investigate the determinants of income inequality and establish the empirical relationship between income inequality and violent crime in Nigeria by using a time series dataset for the period 1990 to 2019. The study examines the long-run relationship between the determinants of income inequality and violent crime using socio-economic factors, and governance indicators such as Real GDP per capita, financial development unemployment rate, education level, the rule of law and political stability. The study utilised the Autoregressive Distributed Lag (ARDL) bound test approach to examine the long-run determinants of income inequality, and to see how it affect violence crime in Nigeria. Income inequality in Nigeria has increased between 1990 and 2019 as confirmed by the Gini coefficient - from 0.26 to 0.51- placing the country among the unequal countries of the world, with its attendant effect sparking regional and community outbreaks of violence and low pace of economic growth. After investigating its determinants in Nigeria, the study found that income, financial development, and educational level are significant determinants of income inequality.. On the relations between income inequality and violent crime, the study found that income inequality is a significant determinant of violent crime rate in Nigeria. The result of control variables shows that unemployment level, education level and political stability are also determinants of violent crime in Nigeria for the period under study. Also, factors that define income inequality determines violent crime rates in Nigeria. Based on the findings of the study, it is apparent that the socio-economic condition accompanied by good governance reduced the level of income inequality as well as the rate of violent crime in Nigeria.